A new Late Triassic phytogeographical scenario in westernmost Gondwana - Cesari, Silvia Nelida (2013)
Floral provincialism within the Southern Hemisphere during the Late Triassic (230 Ma) is characterized by the Ipswich and Onslow provinces, recognized originally in eastern Gondwana. However, new palynological assemblages from the Ischigualasto Formation, northwestern Argentina (231–225 Ma), change the phytogeographic interpretation for the Carnian–Norian in the westernmost Gondwana, which was previously considered part of the southern floral Ipswich province. Here we show the presence of diagnostic Euramerican species within assemblages dominated by Gondwanan taxa that allows us to refer the palynofloras to the Onslow province. Our new data extend the Onslow floral belt, previously recognized from the western edge of Tethys to Timor, to the western margin of South America. This has implications for palaeophytogeography, palaeoclimate reconstructions and the palaeoecology of a Triassic ecosystem, which has yielded significant vertebrate remains and is regarded important in the early evolution of groups such as the Dinosauria.